Linguistic theory and aphasia: an overview - Garraffa, Maria; Fyndanis, Valantis (My University, 2020)
Background: Aphasia research has been informed by linguistic theory to a great extent. Conversely, linguistic theory has also been informed by data from people with aphasia, albeit to a lesser extent. Aims: This overview to the Special Issue of Aphasiology entitled “Aphasia and linguistic theory: What we have captured so far” presents a narrative review that aims to illustrate the contribution of linguistic theory to aphasia research, and also includes a section that presents the articles making up the special issue. The narrative review, which is not exhaustive, highlights influential theoretical frameworks and linguistic constructs that have been central to accounts of language impairment in aphasia. Main Contribution: The overview illustrates the contribution of linguistic theory to aphasiology and paves the way for the development of a unified approach to aphasia, which will incorporate insights not only from theoretical linguistics, but also from other complementary fields, such as psycholinguistics, cognitive (neuro)psychology, and neuroscience of language.
Keywords: Aphasia; Generative grammar; Linguistic theory; Syntax; Usage-based approaches